Photonic Sorting of Aligned, Crystalline Carbon Nanotube Textiles. Issue 1 (December 2017) - Bulmer, John; Gspann, Thurid; Orozco, Francisco; Sparkes, Martin; Koerner, Hilmar; Bernardo, A.; Niemiec, Arkadiusz; Robinson, J.; Koziol, Krzysztof; Elliott, James; O'Neill, William
Abstract Floating catalyst chemical vapor deposition uniquely generates aligned carbon nanotube (CNT) textiles with individual CNT lengths magnitudes longer than competing processes, though hindered by impurities and intrinsic/extrinsic defects. We present a photonic-based post-process, particularly suited for these textiles, that selectively removes defective CNTs and other carbons not forming a threshold thermal pathway. In this method, a large diameter laser beam rasters across the surface of a partly aligned CNT textile in air, suspended from its ends. This results in brilliant, localized oxidation, where remaining material is an optically transparent film comprised of few-walled CNTs with profound and unique improvement in microstructure alignment and crystallinity. Raman spectroscopy shows substantial D peak suppression while preserving radial breathing modes. This increases the undoped, specific electrical conductivity at least an order of magnitude to beyond that of single-crystal graphite. Cryogenic conductivity measurements indicate intrinsic transport enhancement, opposed to simply removing nonconductive carbons/residual catalyst.